2014
DOI: 10.1109/taes.2014.120475
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Nyquist radar prototype: Hardware and algorithm

Abstract: Traditional radar sensing typically employs matched filtering between the received signal and the shape of the transmitted pulse. Matched filtering (MF) is conventionally carried out digitally, after sampling the received analog signals. Here, principles from classic sampling theory are generally employed, requiring that the received signals be sampled at twice their baseband bandwidth. The resulting sampling rates necessary for correlation-based radar systems become quite high, as growing demands for target d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
161
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(162 citation statements)
references
References 31 publications
1
161
0
Order By: Relevance
“…An ADC can not, however, individually acquire each of the randomly chosen Fourier coefficients. Therefore, sub-Nyquist radar prototype in [15] opted for sampling random disjoint subsets of κ, with each subset containing consecutive Fourier coefficients. The prototype in [15] used four random Fourier coefficient groups, pre-filtered the baseband signal to corresponding four subbands (or Xampling slices), and sampled each subband via separate low-rate ADC.…”
Section: A Design Philosophymentioning
confidence: 99%
See 2 more Smart Citations
“…An ADC can not, however, individually acquire each of the randomly chosen Fourier coefficients. Therefore, sub-Nyquist radar prototype in [15] opted for sampling random disjoint subsets of κ, with each subset containing consecutive Fourier coefficients. The prototype in [15] used four random Fourier coefficient groups, pre-filtered the baseband signal to corresponding four subbands (or Xampling slices), and sampled each subband via separate low-rate ADC.…”
Section: A Design Philosophymentioning
confidence: 99%
“…The prototype can be configured either as a filled or thinned array, thereby allowing comparison of Nyquist and sub-Nyquist spatial sampling using the same hardware. Our previous work in [15] presented the hardware realization of spectral sub-Nyquist sampling in radar. In [15], a few randomly chosen, narrow subbands of the received signal spectrum are pre-filtered before being sampled by low-rate analog-to-digital converters (ADCs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the signal itself is not of interest to the application, we might consider an alternative sampling scheme to directly estimate the shift without first reconstructing the signal. These ideas have in fact been recently explored in the context of radar and ultrasound [13], [14], [15], [16] with continuous time signals and multiple shifts. Here we consider a related problem and ask: What is the minimal information rate to shift retrieval when two related discrete-time signals are under-sampled?…”
mentioning
confidence: 99%
“…Furthermore, CSR reduces both the computational load and the number of samples needed in the process. This is of particular interest since recent developments in sampling [17], [18], [19] have shown that Fourier coefficients can be efficiently obtained from space (or time) measurements by the use of an appropriate filter and by subsampling the output. Remarkably, our results also show that in some cases sampling as few as one Fourier coefficient is enough to perfectly recover the true shift.…”
mentioning
confidence: 99%